A critical review on the mimetic theory of René Girard: Politics, religion, and violence. (19th December 2021) - Imran, Muzzamel Hussain; Zhai, Zhihong
Abstract: This paper aims to introduce the mimetic theory of René Girard to explore the connection between culture and religious violence to deal with some critical problems in international affairs. It challenges the narrow conceptualization of the issue of religion and violence as an issue of religious violence. As often as the issue of religion and violence is structured in such a manner, allegedly to pick religion seriously without considering politics or culture seriously. The conception is limited because, as an idea, religion is always contested, negotiated, and developed socially, culturally, or politically. It is a biased interpretation of a world actuality, which under certain conditions grounds violence. Furthermore, this narrow definition of religion suits what critical scholars describe as a problem‐solving strategy to theory. This study demonstrates mimetic theory challenges and reconfigures the conventional interpretation of the issue of religious violence and critically analyse the causes of the hidden, exposed violence as well as the scapegoat mechanism that functions in both domestic cultures as well as in international affairs, maintaining political and cultural order of any society.